1994
DOI: 10.1007/bf00223700
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow between cultivated and wild sunflowers

Abstract: With the development of transgenic crops, concern has been expressed regarding the possible escape of genetically-engineered genes via hybridization with wild relatives. This is a potential hazard for sunflowers because wild sunflowers occur as weeds in fields where cultivated sunflowers are grown and hybridization between them has been reported. In order to quantify the potential for gene escape, two experimental stands of sunflower cultivars were planted at two sites with different rainfall and altitude prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 38 publications
7
123
0
1
Order By: Relevance
“…the capacity of hybridization and the fertility of the hybrids and successive backcrosses, has to be investigated. The possibility of hybridization with a wild relative and the subsequent persistence of crop genes in the wild species have already been demonstrated for several crops; for example sunflower (Arias and Rieseberg 1994;Whitton et al 1998), sorghum Ellstrand 1996, 1997), radish (Lee and Snow 1998) and alfalfa (Jenczewski et al 1999).…”
Section: Relevance Of the Results For The Risk Assessment Of Transgenmentioning
confidence: 96%
“…the capacity of hybridization and the fertility of the hybrids and successive backcrosses, has to be investigated. The possibility of hybridization with a wild relative and the subsequent persistence of crop genes in the wild species have already been demonstrated for several crops; for example sunflower (Arias and Rieseberg 1994;Whitton et al 1998), sorghum Ellstrand 1996, 1997), radish (Lee and Snow 1998) and alfalfa (Jenczewski et al 1999).…”
Section: Relevance Of the Results For The Risk Assessment Of Transgenmentioning
confidence: 96%
“…A number of studies documented the introgression and persistence of cultivar alleles in wild relatives (1,8,9,14,17). Several factors assist exchange of genes between wild and cultivated sunflowers: overlapping of flowering time, shared pollinators, self-incompatibility of wild sunflower, self compatibility of domesticated sunflower, and high rate of outcrossing.…”
Section: Cms Lines For Evaluation Of Pollen Flow In Sunflower Relevanmentioning
confidence: 99%
“…The evidence for long distance pollen flow was obtained in other studies. Arias and Rieseberg (1) found that pollen from cultivated sunflower can be spread over a distance of 1 km and to pollinate the wild sunflowers. Pollen flow at long distances was also observed in canola (Brassica napus), which is pollinated by wind and insects.…”
Section: Genotyping Of Sunflower Linesmentioning
confidence: 99%
“…Early studies mainly focused on gene flow into crop strains because of fears that seed lots would be contaminated by foreign germplasm (Sprague 1938;Crane & Mather 1943;Haskell 1943;Bateman, 1947a, b, c;Jones 1948;Hutchcroft 1955;Nieuwhof 1963). More recently, concern has been expressed regarding gene flow from crop plants into their wild relatives via hybridization (Arias & Rieseberg 1994).…”
Section: Introductionmentioning
confidence: 99%